Primary Pancreatic Lymphoma or Secondary Involvement: What Is the Difference? - Kav, Taylan; Soyuoz, Aynur G; Altundag, Kadri; Bayraktar, Yusuf (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: A mass of the pancreas invading the nearby surrounding soft tissues.